Avaliação do processo foto-fenton induzido com o complexante orgânico ácido oxálico para o tratamento de lixiviado de aterros sanitários - Leichtweis, Jandira (2017)
Landfill leachate presents high pollutant potential that could manage soil and water sources, being considered the main drawback of sanitary landfills. This liquid derived by the solid wastes degradation needs to be treat before being released in the nature. As an alternative to treat this wastewater, AOPs arises, highlighting the photo-Fenton Process (PFP), being noted that other techniques of treatment like physical separation and biological oxidation in some cases aren’t completely efficient to degrade the recalcitrant pollutants presented by the landfill leachate, unable to reach the wastewater standards of release. However, recent studies display a reduction of the PFP efficient when applied to the treatment of wastewaters that present high organic load and dissolved solids, which could be related to not dissolution and precipitation of the ion iron, due to its complexation with pollutants present in the wastewaters. Therefore, as an alternative technique of treatment the employment of chelate agents is proposed, in order to form strong and stables complexes with Fe 3+ such as oxalic acid (ferrioxalate). Thereby, this research aimed to study the treatment of landfill leachate employing the PFP mediated by acid oxalic. It was evaluated the method to form the complex between iron and chelate in order to treat landfill leachate. The main reaction operational parameters: solution pH (2.2; 3; 5; 7; 7.8), iron concentrations (48, 60, 90, 120 e 132 mg Fe L -1 ), oxalic concentration, H 2 O 2 consumed and UV required energy were evaluated drawing on a lab- scale photo-reactor handling and batch system, exposed to artificial UV-Vis irradiance. In order to determine the best performance of the treatment employed in a lab-scale reactor, the reduction of color (%) and Abs 254 nm (%) were chosen as response variables. Reactions mediated in 2.2 and 2.8 pH solution were limited due some drawbacks such as: precipitation and/or volatilization of humic acids in the acidification step and the formation of complexes with iron and organic load present in the landfill leachate. Thus, it was found that these results weren’t regard photo-oxidation, and just related to the initial stage of acidification followed by a simple phase transfer among pollutants. However using the complex ferrioxalate, it was possible to obtain favorable degradation rates with the solution pH near to neutral, eliminating the acidification step. The best results were found employing [Fe 3+ ] 90 (mg L -1 ) and solution pH 7.8, because with these conditions was possible to maintain pollutants in solution able to be oxidized, achieving 52.5 and 47.0 % of reduction of color and Abs 254 nm, respectively, consuming around 220 mM of H 2 O 2 .